2017
DOI: 10.1016/j.celrep.2017.10.063
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Modulates Nociception as an Agonist of Pain-Sensing TRPV1

Abstract: SUMMARY Oxytocin is a hormone with various actions. Oxytocin-containing parvocellular neurons project to the brainstem and spinal cord. Oxytocin release from these neurons suppresses nociception of inflammatory pain, the molecular mechanism of which remains unclear. Here, we report that the noxious stimulus receptor, TRPV1, is an ionotropic oxytocin receptor. Oxytocin elicits TRPV1 activity in native and heterologous expression systems, irrespective of the presence of the classical oxytocin receptor. In TRPV1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
89
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 37 publications
4
89
1
1
Order By: Relevance
“…Oxytocin has also been reported to act not only on the oxytocin receptor, but also on vasopressin receptors, on δ subunit-containing GABA A receptors 276 and on transient receptor potential vanilloid (TRPV1). 277 Although pharmacological studies have shown the importance of vasopressin receptors in the actions of oxytocin, 278 molecular and genetic evidence directly showing the roles of vasopressin receptors is not sufficient. 279,280 The physiological roles of these receptors in the actions of oxytocin remain to be clarified.…”
Section: Con Clus Ionsmentioning
confidence: 99%
“…Oxytocin has also been reported to act not only on the oxytocin receptor, but also on vasopressin receptors, on δ subunit-containing GABA A receptors 276 and on transient receptor potential vanilloid (TRPV1). 277 Although pharmacological studies have shown the importance of vasopressin receptors in the actions of oxytocin, 278 molecular and genetic evidence directly showing the roles of vasopressin receptors is not sufficient. 279,280 The physiological roles of these receptors in the actions of oxytocin remain to be clarified.…”
Section: Con Clus Ionsmentioning
confidence: 99%
“…It appears oxytocin may have anti-nociceptive capabilities via TRPV1 receptors, thus alterations in oxytocin levels induced by cadmium exposure may also change the nociceptive properties in tobacco exposed CH patients, making them more susceptible to headaches at certain times of the year when hypothalamic dysfunction occurs. 46 Modulator of Pituitary Hormones Linked to CH. Recent studies in rat models demonstrate that low concentrations of cadmium via its xenoestrogenic activity can stimulate PRL secretion and cell growth from the anterior pituitary.…”
Section: Question 2: What Toxins In Cigarette Smoke Lead To Cluster Hmentioning
confidence: 99%
“…36 In most instances testosterone levels are low in CH patients both in and out of cycle. 46 Modulator of Pituitary Hormones Linked to CH. 37 In female rodents, estrogen tonically inhibits the expression of orexin, and estrogen replacement will normalize very elevated orexin levels in postmenopausal women.…”
mentioning
confidence: 99%
“…Frog and rabbit TRPV1 channels are less sensitivite to capsaicin, (Gavva et al, 2004; Ohkita et al, 2012) and the chicken TRPV1 shows the least sensitivity (Jordt and Julius, 2002). The pharmacological characteristics of TRPV1 provides the understanding to efficiently target, activate and inhibit the channel, which may be one of the strategies to design analgesic drugs (Brito et al, 2014; Nersesyan et al, 2017; Szallasi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%